Colombian SMEs in the coal mining sector: financial performance analysis (2014- 2019) (Revista cientifica In Vestigium Ire, 2021)
The objective of this research is to evaluate the financial performance of small and medium-sized companies in the coal mining sector in Colombia in the period 2014-2019, having as methodology the analysis of accounting and value management indicators that account for their growth, efficiency,efficiency and effectiveness. It is found that the coal mining SME achieves in the six-year period an accounting performance, being superior in the small company for being more efficient in the use of assets and more effective in the management of all costs and expenses, even without being the most effective in the management of operational disbursements, nor the one that uses greater financial leverage. Nevertheless, the SME destroys economic value added (EVA) in the period, although in the medium-sizedcompany this destruction is less. When comparing the SME with the entire coal sector, it is found that its effectiveness as measured by return on equity is lower, as is its efficiency in managing all costs and expenses, but the destruction of value, in relative terms, is still lower in the medium-sized company.
Keywords: EVA; Market value added (MVA); Return on assets (ROA); Return on equity (ROE); SME; Coal mining sector